2016
DOI: 10.1080/01431161.2016.1226527
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for detection and counting of oil palm trees using high-resolution multispectral satellite imagery

Abstract: In the past, oil palm density has been determined by manually counting trees every year in oil palm plantations. The measurement of density provides important data related to palm productivity, fertilizer needed, weed control costs in a circle around each tree, labourers needed, and needs for other activities. Manual counting requires many workers and has potential problems related to accuracy. Remote sensing provides a potential approach for counting oil palm trees. The main objective of this study is to buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 28 publications
0
16
0
3
Order By: Relevance
“…It employs similar steps, which include the implementation of a Sobel edge detector, texture analysis co-occurrence, dilation, eroding, high-pass, and opening filters. The researchers were able to achieve an equally good overall accuracy of 90%-95% (Santoso, Tani, and Wang 2016).…”
Section: Change Detectionmentioning
confidence: 84%
“…It employs similar steps, which include the implementation of a Sobel edge detector, texture analysis co-occurrence, dilation, eroding, high-pass, and opening filters. The researchers were able to achieve an equally good overall accuracy of 90%-95% (Santoso, Tani, and Wang 2016).…”
Section: Change Detectionmentioning
confidence: 84%
“…Korom et al [17] found a lower detection accuracy of oil palm trees of 77% post-watershed segmentation and masking non-oil palm trees using WorldView-2 satellite image. In addition, Santoso et al [13] used different pan-sharpening methods on QuickBird image to detect oil palm trees. They found that the accuracy of detection was 100% with the modified intensity-hue-saturation (IHS) pan-sharpening, 99.5% with normalized color (Brovey) pan-sharpening, 99.8% subtractive resolution merge pan-sharpening and 99.3% principal components (PC) spectral sharpening.…”
Section: Detection Accuracymentioning
confidence: 99%
“…To study the relationship between infestation and tree density, we need to count the number of trees in each area. Tree counting used to be done manually, but that required significant efforts and costs [9][10][11], and was susceptible to errors, especially in non-systemic fields where rows overlap and trees are of different sizes and ages [12,13]. Researchers have innovated many automatic and semi-automatic approaches for detecting single trees from high spatial resolution images of different types of sensors [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of classifier are able to model complex problems in which they perform better than the other approaches (LeCun, 2015). This deep learning approach was used on satellite imagery and has already demonstrated its ability to detect and localize oil palms under homogeneous and aligned planting conditions (Li et al, 2016 andSantoso, 2016). It remains to test deep learning approach on more heterogeneous areas, such as in oases and urban areas, where RPW is more difficult to detect and monitor.…”
Section: Introductionmentioning
confidence: 99%